1991
DOI: 10.1139/g91-123
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of repetitive DNA sequences from genomes of Oryza minuta and Oryza australiensis

Abstract: The value of genome-specific repetitive DNA sequences for use as molecular markers in studying genome differentiation was investigated. Five repetitive DNA sequences from wild species of rice were cloned. Four of the clones, pOm1, pOm4, pOmA536, and pOmPB10, were isolated from Oryza minuta accession 101141 (BBCC genomes), and one clone, pOa237, was isolated from Oryza australiensis accession 100882 (EE genome). Southern blot hybridization to different rice genomes showed strong hybridization of all five clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The presence of strong distinct signals in the hybridized lanes suggested that there are several families of DNA repeat sequences specific to the genome(s) of the two species complexes. The presence of genome-specific repeat sequences has been demonstrated for almost all the known genomes in rice (Zhao et al 1989;Aswidinnoor et al 1991). The relative abundance and distribution of such genome-specific repeat sequences are probably central to the observed high degree of divergence in these genomes.…”
Section: Divergence Of O Ridleyi and O Meyeriana Complex Speciesmentioning
confidence: 99%
“…The presence of strong distinct signals in the hybridized lanes suggested that there are several families of DNA repeat sequences specific to the genome(s) of the two species complexes. The presence of genome-specific repeat sequences has been demonstrated for almost all the known genomes in rice (Zhao et al 1989;Aswidinnoor et al 1991). The relative abundance and distribution of such genome-specific repeat sequences are probably central to the observed high degree of divergence in these genomes.…”
Section: Divergence Of O Ridleyi and O Meyeriana Complex Speciesmentioning
confidence: 99%
“…Genomic-specific repetitive DNA sequences have also been cloned and characterized in other plants such as rice (Oryza spp.) (Aswidinnoor et al 1991). These sequences may be useful in monitoring alien gene introgression between species.…”
Section: Different Hybridizing Patterns In Various Speciesmentioning
confidence: 99%
“…Recently molecular markers have been utilized to study the genome differentiation in various plant species. Both single-copy (Song et al, 1988;Bonierbale et al, 1988) and repetitive DNA sequences (Aswidinnoor et al, 1991;Anamthawat-Jonsson andHeslop-Harrison, 1993 andMawal et al, 1995) have been used. Repetitive DNA is the major determinant of plant chromosome structure and of the nucleotype.…”
Section: Introductionmentioning
confidence: 99%